A Note on the Appell Hypergeometric Matrix Function F2. (31st March 2020) - Hidan, M.; Abdalla, M.
Abstract : In this article, we introduce some of the mathematical properties of the second Appell hypergeometric matrix function F 2 ( A, B 1, B 2, C 1, C 2 ; z, w ) including integral representations, transformation formulas, and series formulas.